Electron Beam Irradiation: Exchange Bias Effect in Epitaxial LaMnO3+δ Film Induced by Electron Beam Irradiation (Adv. Mater. Interfaces 2/2020). Issue 2 (23rd January 2020) - Xue, Mingzhu; Ding, Shilei; Lai, Youfang; Li, Xin; Zha, Liang; Peng, Yuxuan; Liang, Zhongyu; Yang, Wenyun; Men, Yong; Kong, Xiangdong; Han, Li; Chen, Xuegang; et al.
Abstract : Exchange bias induced by the interfacial coupling of the antiferromagnetic/ferromagnetic heterojunction plays a critical role in spintronic devices. In article number 1901296 by Xuegang Chen, Jinbo Yang and co‐workers, an interesting exchange bias effect is reported in the ferromagnetic LaMnO3 films (blue) with antiferromagnetic clusters (red) induced by electron beam irradiation.